PENERAPAN STRATEGI MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPS KELAS IV DI MIN 1 PONTIANAK - Maulidiyaturrahmah, Maulidiyaturrahmah; Rianawati, Rianawati; Muthmainnah, Fitri Muthmainnah; Yulianti, Desi (Jurnal Karya Ilmiah Pendidik dan Praktisi SD&MI (JKIPP), 2024)
This research aims to describe: (1) Student learning outcomes before implementing the make a match strategy. (2) Steps for implementing the make a match strategy to improve student learning outcomes. (3) Student learning outcomes after implementing the make a match strategy. (4) Increased student learning outcomes after implementing the make a match strategy. Based on the research results, it can be concluded that: 1) The learning outcomes before implementing the make a match strategy were an average of 64.88 and 49% or 21 students who completed, 2) This research was carried out in two cycles. In cycle I, the advantage was that the teacher was quite optimal in implementing the make a match strategy steps. Meanwhile, the weakness in cycle I was that the teacher in dividing the time allocation was not optimal. In cycle II the teacher's activities have increased and are very good in terms of the learning steps carried out, 3) Learning outcomes after implementing the make a match strategy in cycle I were 65% or 28 students who achieved a completeness score with an average score of 73.72 , and cycle II was 86% or 37 students who achieved completeness with an average score of 85.35, 4) There was an increase in student learning outcomes after implementing the make strategy a match with a completion percentage from 49% to 86% with an average value before applying the make a match strategy, namely 64.88, increasing to 85.35.